A Comprehensive Literature Review of Complication Rates of Central Venous Catheters - Stefanie, Stefanie; Wahyu, Wahyu; Muhammad Indra, Muhammad Indra (The International Journal of Medical Science and Health Research, 2024)
Background: The literature on the complication rates of central venous catheters (CVCs) reveals a complex interplay of risks associated with their use, particularly in vulnerable patient populations such as those with cancer or undergoing hemodialysis. The foundational work by (Schumacher & H. Wagner, 2007) established the significance of implanted central venous port catheter systems, pointing out the persistent challenges of catheter-associated thrombosis and infections. This early recognition of complications set the stage for subsequent studies that have consistently reported high complication rates, ranging from 10-25% among cancer patients as highlighted by (Marin et al., 2021). Literature Review: The complications associated with CVCs extend beyond mere infection and thrombosis; they encompass a range of insertion-related issues including arrhythmias and arterial punctures, as discussed by (Hodzic et al., 2014). Innovation in catheter design has been explored as a potential solution to mitigate infection rates. The review by (Casimero et al., 2020) stresses the importance of selecting the appropriate catheter type based on patient-specific factors, thereby minimizing complications. The impact of the COVID-19 pandemic on CVC complications was notably addressed by (Tanveer Ud Din et al., 2021), which illustrated how procedural lapses during high-pressure situations can exacerbate the risks associated with CVC placement. Conclusion: In conclusion, the literature collectively underscores the multifaceted complications associated with CVCs and emphasizes the need for ongoing research and innovation to improve patient outcomes. The findings highlight the importance of tailored management strategies, adherence to procedural protocols, and the continuous development of catheter technology to mitigate risks associated with CVC use.